PENGARUH PENGGUNAAN APLIKASI PENGINGAT TERHADAP KEPATUHAN MINUM TABLET FE DAN STATUS ANEMIA IBU HAMIL: ARTIKEL REVIEW - Krismawati, Endang; Widjanarko, Bagoes; Rahfiludin, M.Z (Poltekkes Kemenkes Semarang, 2021)
Background: Maternal Mortality Rate (MMR) is an indicator to see the success of maternal health efforts. The results of the 2018 Riskesdas stated that in Indonesia, 48.9% of pregnant women had anemia. 84.6% of anemia in pregnant women occurs in the 15-24 year age group. To prevent anemia, every pregnant woman is expected to get a blood supplement (TTD) of at least 90 tablets during pregnancy. The coverage of giving iron tablets to pregnant women in Indonesia in 2019 was 64.0%. This figure has not reached the 2019 Strategic Plan target of 98%. The low compliance of pregnant women in drinking iron tablets requires a meditation application to help remind them to drink iron tabletsThe aim of the studyÂ : was to analyze the effect of the Pregnant Women Friend Application (ASIH) on compliance with Fe tablets and anemia status of pregnant womenMethods: Design This study is an analytical study with experimental design. The population in this study were all pregnant women in Indonesia.Results: Adherence to taking iron tablets increased after being given the application. The statistical test proved that the application had an effect on adherence to drinking iron tablets (P value = 0.000). : Anemia status has decreased after being given the application. The statistical test proved that the application had an effect on anemia status (P value = 0.000).Conclusion: Compliance of pregnant women taking iron tablets and anemia status after using the application was higher, compared to before using the application